ChemInform Abstract: Valorization of Industrial Waste and By‐Product Streams via Fermentation for the Production of Chemicals and Biopolymers. Issue 22 (3rd June 2014) - Koutinas, Apostolis A.; Vlysidis, Anestis; Pleissner, Daniel; Kopsahelis, Nikolaos; Lopez Garcia, Isabel; Kookos, Ioannis K.; Papanikolaou, Seraphim; Kwan, Tsz Him; Lin, Carol Sze Ki
Abstract Review: 305 refs.